A Collage of Experiences: Bivouac Literature and Catalan Testimony from the Trenches of the Great War. Issue 7 (9th August 2021) - Aulet, Francesc Montero
Abstract: This article analyses testimonies of Catalan soldiers involved in the First World War despite official Spanish neutrality, whose fragmented impressions appeared in a kind of collage in contemporary periodicals. Carefully interpreted to put into perspective the idealization and epicism of the combatants, they constitute egodocuments with diary-like components that are of great value for our understanding of everyday life in the trenches. They also demonstrate that the collaboration of Catalans with the Allied cause was not only human and intellectual, but also literary, through testimony of a high standard, comparable to the great European works generated by the war.